The Effect of Mg Foliage Fertilization on Beetroot (Beta vulgaris ssp. esculenta var. rubra) Morphology, Quality Traits and their Relations - Takácsné Hájos, Mária; Szőllősiné Varga, Ilona (Acta Agraria Debreceniensis, 2004)
Mg-treatment increased solid soluble content in roots probably due to the larger assimilation area.The applied foliage fertilization affected inner colour intensity and uniformity in roots positively.The 2% Mg-sulphate solution affected pigment quantity favourably depending on varieties.Close correlation (r=0,71) was found between the yellow (BX) and red (BC) pigments which indicates a similar biosynthetic pathway of the two compounds.The Mg-sulphate foliage fertilization improves quality considerably but the individual reaction of varieties needs further studies.